Praktik Etika Bisnis Islam dan Maqashid Syariah pada Industri Kecil Menengah Griya Pangan Batang - Rohmah; Adinugraha, Hendri Hermawan; Muhtarom, Ali (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2023)
Intense business competition has made many business people justify any means to get big profits, many of them often forget Islamic business ethics and social responsibility. Therefore, through this research there is a need for an in-depth study of Islamic business ethical practices and maqashid sharia in IKM (Small and Medium Industries) Griya Pangan Batang. This type of research is qualitative with a field research approach. The research location is IKM Griya Food Batang in Terban Village, RT 09 RW 07, Warungasem District, Batang Regency. This research began with interviews in September 2022 until June 2023. Primary data sources in this study include information from interviews with parties related to this problem, in this case, namely ten active members of the IKM Griya Pangan Batang as the main informant, and the additional informant, namely the Buyer, and the Disperindagkop Party. Secondary data sources are books and various relevant references regarding related themes seen from the Maqashid Syariah perspective. Data collection and analysis techniques use the triangulation method. The results of this research conclude that IKM Griya Pangan Batang has implemented Islamic business ethics with the principles of divinity, justice, honesty and free will, However, in principle, divinity and virtue are still not perfect. IKM Griya Pangan Batang has implemented Islamic business ethics in the perspective of maqashid sharia well, has been able to protect religion, protect souls, protect minds, protect offspring, although it has not fully been able to protect assets properly. Islamic business ethics and sharia maqashid have an impact on the business culture at IKM Griya Pangan Batang which is more oriented to integrity and morality.